Pencemaran Mikroplastik di Sungai: Suatu Tinjauan Sosiologis Terhadap Perilaku Menyimpang Pengelolaan Sampah Di Masyarakat - Arifah, Zahra; Nurdin, Ibnu Phonna; Cut Lusi Chairun Nisak; Dara Fatia; Firdaus Mirza Nusuary (Dynamics of Rural Society Journal, 2024)
Microplastics will cause serious health problems if they are consumed by living creatures. The public's unwittingly disposing of garbage leads to increasing amounts of microplastic waste every day. The objective of the research is to examine the presence of microplastics in living creatures and to analyse what factors are causing society to engage in these non-conformist actions. The study was carried out on the Aceh Krueng River (Lambaro Bridge) in Greater Aceh district. Data was collected through in-depth interviews and observations of communities in the surrounding area. Research findings suggest that there are several kinds of plastic garbage found around the Lambaro Bridge riverway, such as: a. plastic packaging trash; and b. plastic glass trash. The effects of microplastics on living creatures are: a. for fish, they will affect a decrease in appetite and have a high potential for death. b. for zooplankton, affecting digestive disorders and acute and chronic effects of zooplanton. c. impact on humans, i.e., inflammation of organs and intestinal microbial disorders. The existence of plastic garbage is caused by non-conforming behaviour in the community, i.e., a. dumping in the river has become a bad habit; b. lack of public concern for the environment due to poor education; c. minimal interest in selling plastic waste to the wrappers; d. no punishment for the perpetrators of discreetly disposing of plastic waste; and e. minimum means and facilities of TPA in some locations